Histopathological Study of Epithelial, Melanocytic And Adnexal Tumors Of Skin- A Retrospective Study In A Tertiary Care Centre - Pitla, Sandhya; Dara, Vijayasri (Annals of Pathology and Laboratory Medicine, 2021)
Background and objectives: To classify and identify various skin tumors and study their variations according to age and sex. The most common predisposing factors being fair skin, sun exposure, chemical exposure, HPV infection in the setting of immunosuppression. Methods: This was an observational study carried out in the Department of Pathology at private Medical College of coastal Andhra from July 2018 to June 2020. Result: The present study included histopathological study of 71 cases of tumors of skin and its adnexae over a period of two years. Out of the 71 tumors, 43 were diagnosed as benign and 28 as malignant tumors of skin constituting 61% and 39% respectively. The ratio of benign to malignant tumors was 1:0.63. Among the 43 benign tumors 20 (46.5%) were tumors of skin appendages, 15 (34.9%) were tumors of epidermis, 8 (18.6%) were of melanocytic origin. Among the 28 malignant tumors 25 (89.3%) were tumors of epidermis, 2 (7.1%) were melanocytic tumors and 1 (3.6%) was tumor of skin appendages. Among the malignant epidermal tumors squamous cell carcinoma was the most common constituting 42.9% (12 cases). Conclusion: The present study concludes that benign tumors are most common when compared to malignant tumors of skin. Among the malignant tumors, Squamous cell carcinoma falls as the most common variety of skin followed by Basal cell carcinoma and verrucous carcinoma. Among the benign tumors, tumors of epidermal origin are most frequent followed by tumors of sweat gland and adnexal-hair follicle origin.